2004
DOI: 10.1093/annonc/mdh064
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exemestane on serum lipid profile in postmenopausal women with metastatic breast cancer: a companion study to EORTC Trial 10951, ‘Randomized phase II study in first line hormonal treatment for metastatic breast cancer with exemestane or tamoxifen in postmenopausal patients’

Abstract: Overall, exemestane has no detrimental effect on cholesterol levels and the atherogenic indices, which are well-known risk factors for coronary artery disease. In addition, it has a beneficial effect on TRG levels. These data, coupled with E's excellent efficacy and tolerability, support further exploration of its potential in the metastatic, adjuvant and chemopreventive setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The increase in LDL-C may therefore be at least partially explained by the loss of the positive action of tamoxifen. The decrease in HDL-C in the exemestane group is in line with previous studies, and may be explained by a direct action of exemestane and/or by the interruption of tamoxifen therapy (Atalay et al, 2004;Lonning et al, 2005;Markopoulos et al, 2005;Esteva and Hortobagyi, 2006). The Intergroup Exemestane Study found a trend toward more frequent myocardial infarction in patients treated with exemestane than in those treated with tamoxifen (Coombes et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The increase in LDL-C may therefore be at least partially explained by the loss of the positive action of tamoxifen. The decrease in HDL-C in the exemestane group is in line with previous studies, and may be explained by a direct action of exemestane and/or by the interruption of tamoxifen therapy (Atalay et al, 2004;Lonning et al, 2005;Markopoulos et al, 2005;Esteva and Hortobagyi, 2006). The Intergroup Exemestane Study found a trend toward more frequent myocardial infarction in patients treated with exemestane than in those treated with tamoxifen (Coombes et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, it has recently been suggested that women receiving aromatase inhibitors for breast cancer prevention may be at increased risk of cardiovascular diseases, because the oestrogen-lowering effects of such drugs may have adverse effects on blood lipids (Baum et al, 2003;Goss et al, 2003;Atalay et al, 2004;Esteva and Hortobagyi, 2006;Markopoulos et al, 2005). Our data showed a significant increase in LDL-C in the patients treated with exemestane: this finding may seem to differ from those of other studies indicating that exemestane has a neutral effect on LDL-C, but it must be remembered that our patients had been treated with tamoxifen for at least 2 years, which markedly reduces LDL-C levels (Love et al, 1990;Atalay et al, 2004;Esteva and Hortobagyi, 2006;Markopoulos et al, 2005). The increase in LDL-C may therefore be at least partially explained by the loss of the positive action of tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, research indicates a possible causal effect of PCBs on serum lipid levels (Hennig et al 2005; Langer et al 2003). Additionally, lipid levels have been suggested to affect breast cancer risk (Atalay et al 2004), but their impact on other health end points has received limited attention. For our purposes in this study, our scenarios, hypothetical “causal truths,” are based on the literature and their relation to frequently used statistical models.…”
Section: Methodsmentioning
confidence: 99%